Early polymerase chain reaction detection of Chagas disease reactivation in heart transplant patients - Costa, Priscilla Almeida da; Segatto, Marcela [UNESP]; Durso, Danielle Fernandes; Carvalho Moreira, Wagson Jose de; Junqueira, Lucas Lodi; Castilho, Fabio Morato de; Andrade, Silvio Amadeu de; Gelape, Claudio Leo; Chiari, Egler; Teixeira-Carvalho, Andrea; Junho Pena, Sergio Danilo; Machado, Carlos Renato; et al. (Elsevier B.V., 2017)
BACKGROUND: Heart transplantation is a valuable therapeutic option for Chagas disease patients with severe cardiomyopathy. During patient follow-up, the differential diagnosis between cardiac transplant rejection and Chagas disease infection reactivation remains a challenging task, which hinders rapid implementation of the appropriate treatment. Herein we investigate whether polymerase chain reaction (PCR) strategies could facilitate early detection of Trypanosoma cruzi (T cruzi) in transplanted endomyocardial biopsies (EMBs). METHODS: In this study we analyzed 500 EMB specimens obtained from 58 chagasic cardiac transplant patients, using PCR approaches targeted to nuclear (rDNA 24S alpha) and kinetoplastid (kDNA) markers, and compared the efficiency of these approaches with that of other tests routinely used. RESULTS: T cruzi DNA was detected in 112 EMB specimens derived from 39 patients (67.2%). The first positive result occurred at a median 1.0 month post-transplant. Conventional histopathologic, blood smear and hemoculture analyses showed lower sensitivity and higher median time to the first positive result. Patient follow-up revealed that 31 of 39 PCR-positive cases presented clinical reactivation of Chagas disease at different time-points after transplantation. PCR techniques showed considerable sensitivity (0.82) and specificity (0.60), with area under the receiver operating characteristic (ROC) curves of 0.708 (p = 0.001). Moreover, PCR techniques anticipated the clinical signs of Chagas disease reactivation by up to 36 months, with a median time of 6 months and an average of 9.1 months. CONCLUSIONS: We found a good association between the PCR diagnosis and the clinical signs of the disease, indicating that the PCR approaches used herein are suitable for early diagnosis of Chagas disease reactivation, with high potential to assist physicians in treatment decisions. For this purpose, an algorithm is proposed for surveillance based on the molecular tests. (C) 2017 International Society for Heart and Lung Transplantation. All rights reserved.
Keywords: Chagas disease reactivation; endomyocardial biopsy; heart transplantation; molecular diagnostics; polymerase chain reaction